Variations in progesterone and estradiol across the menstrual cycle predict generosity toward socially close others. (June 2022) - Sellitto, Manuela; Kalenscher, Tobias
Abstract: The human tendency to share goods with others at personal costs declines across the perceived social distance to them, an observation termed social discounting . Cumulating evidence suggests that social preferences are influenced by the agent's neurohormonal state. Here we tested whether endogenous fluctuations in steroid hormone compositions across the menstrual cycle were associated with differences in generosity in a social discounting task. Adult healthy, normally-cycling, women made incentivized decisions between high selfish rewards for themselves and lower generous rewards for themselves but also for other individuals at variable social distances from their social environment. We determined participants' current levels of menstrual-cycle-dependent steroid hormones via salivary sampling. Results revealed that the increase in progesterone levels as well as the decrease in estradiol levels, but not changes in testosterone or cortisol, across the menstrual cycle, accounted for increased generosity specifically toward socially close others, but not toward remote strangers. Highlights: Generosity toward others declines across the perceived social distance to them. Adult healthy women made incentivized decisions between selfish and generous rewards. Menstrual-cycle-dependent steroid hormone levels were measured via salivary sampling. Increase in progesterone and decrease in estradiol predicted increased generosity. Generosity increased toward socially close others but not toward remote strangers.